ANALISIS KAPASITAS DAN TINGKAT KETAHANAN DAERAH DALAM UPAYA PENGURANGAN RISIKO BENCANA DI KECAMATAN JAYA BARU KOTA BANDA ACEH - Herizal Fakhri; Safrida .; Nazaruddin . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Jaya Baru sub-district, Banda Aceh, geographically an area which faced marine waters, this reason makes Jaya Baru one of the disaster-prone areas, especially tsunami disaster. This study aims to gain an overview of the capacity and resilience of Jaya Baru sub-districts in facing the disaster. Furthermore, to obtain the strategies necessary to increase the capacity and resilience in disaster risk reduction efforts. This study uses a combination method that is combining quantitative and qualitative methods and using five villages in Jaya Baru sub-district as the sample of research i.e. Gampong Ulee Pata, Lamjamee, Lampoh Daya, Emperom, and Bitai. Sources of the data in this study consisted of primary data (field research) and secondary data (library research) as supporting data. The results obtained from the data analysis process shows that Jaya Baru sub-districts categorized as 'medium' in the effort of disaster risk reduction. In addition, for the resilience of the region is at 'level three', i.e. commitment of the government, community and community related to disaster risk reduction has been achieved and supported by policy, but the achievement is not enough to reduce the negative impact of disaster that will happen in the future. Strategies undertaken in disaster risk reduction and capacity building in Gampong Ulee Pata, Lamjamee, Lampoh Daya, Emperom and Bitai must go through the individual level, the organizational level, and the system level.